KONFLIK PEMBEBASAN LAHAN PEMBANGUNAN BENDUNGAN JATIGEDE DI DESA WADO - Amalia, Muthi; Malihah, Elly (Universitas Pendidikan Indonesia, 2016)
The research talks about the conflict of the land acquisition of Jatigede dam construction at Wado, Sumedang. This research has a purpose to know how the process of a land acquisition is, the causative factors of a land acquisition, the impacts of a land acquisition and the conflict resolution for the land acquisition of Jatigede dam construction in Wado. This research usedqualitative approach and case study method. The data collected with observation technique, deep interview and documentation study. The research informant consists of the land acquisition committee, the institution in Wado,the society figure and the people who got the impact. The result of this research shows that the process of a land acquisition make horizontal conflict and vertical conflict come up which caused by the individual differences and had a impact on social system and society economic. Active participation and teamwork is the most effective effort in solving the conflict of the land acquisition of Jatigede dam construction.